A Pharmacological Overview of Alpinumisoflavone, a Natural Prenylated Isoflavonoid - Ateba, Sylvin Benjamin; Mvondo, Marie Alfrede; Djiogue, Sefirin; Zingué, Stéphane; Krenn, Liselotte; Njamen, Dieudonné (Frontiers in Pharmacology, 2019)
Over the last decade, several studies demonstrated that prenylation of flavonoids enhances various biological activities as compared to the respective nonprenylated compounds. In line with this, the natural prenylated isoflavonoid alpinumisoflavone (AIF) has been explored for a number of biological and pharmacological effects (therapeutic potential). In this review, we summarize the current information on health-promoting properties of AIF. Reported data evidenced that AIF has a multitherapeutic potential with antiosteoporotic, antioxidant and anti-inflammatory, antimicrobial, anticancer, estrogenic and antiestrogenic, antidiabetic, and neuroprotective properties. However, research on these aspects of AIF is not sufficient and needs to be reevaluated using more appropriate methods and methodology. Further series of studies are needed to confirm these pharmacological effects, and this review should lay the basis for the design of respective investigations. Overall, despite the drawbacks of studies recorded, AIF exhibits a potential as drug candidate.